KEMAMPUAN DAN PEMANFAATAN KREDIT OLEH IRT DALAM UPAYA PENGEMBANGAN USAHA: PADA PENGUSAHA KRIPIK TEMPE - Haryanto, Sugeng (University of Merdeka Malang, 2008)
This research explained the ability and the credit use in home made business namelytempe crispy chips. The sample of this research was home made business in Tugu sub district,Trenggalek regency that made tempe crispy chips. Credit for business was a factor which hada very important role in supporting the increase of a business. Credit giving was an injectionhoped to create capital for people economy activity and to increase production. This researchintended to 1) know the ability of home made industry in taking credit from micro financeunit, and 2) know the credit used by home made industry in increasing the business. Homemade industry had an ability to take credit from a bank. They all had accepted credit fromlocal government distributed through BPR (people Credit Bank) namely credit program. Credituse was not only used for increasing business but also for fulfilling other household needs.